Food systems after Covid-19 - Ebata, Ayako; Nisbett, Nicholas; Gillespie, Stuart (Institute of Development Studies, 2021)
Measures to slow down the spread of Covid-19 have had profound effects on the food and nutrition security of poor and marginalised households and communities. This article provides an overview of the effects of Covid-19 on food systems across low- and middle-income countries using resilience and political economy lenses, before proposing approaches to build back resilient and equitable food systems. First, future interventions need to target structural issues that limit people’s agency in accessing nutritious and diverse food and production capital. Second, local innovation systems and institutions require investment to create a market environment that benefits domestic (small and medium) enterprises and agri‑food supply chain workers without jeopardising the environment. Third, interventions need to be informed by a diverse set of opinions that include the voices of the most marginalised.